FOOD SELF-SUPPLY IN NEW CONSUMER TRENDS - Paulina Trębska (Polityki Europejskie, Finanse i Marketing)
The article presents premises inscribing food self-supply in new trends occurring in consumer behavior and shows the opinions of consumers on food self-supply. The analysis used research conducted in 2017 in the Mazowieckie voivodship among representatives of rural households. Food self-supply is part of the concept of sustainable development and sustainable consumption. It is an example of the greening of consumption, and of conscious and collaborative consumption. The most important factors entering food self-supply into new consumer trends are natural and healthy food produced in accordance with sustainable development, care for health and the natural environment, cultivating traditions, but also product individualization related to the use of free time.